Implementasi RAD Pada Pengembangan Website Halo Gamers - SOPHYA HADINI MARPAUNG (JSAI (Journal Scientific and Applied Informatics), 2025)
The presence of Key Opinion Leaders (KOL) is increasingly important in the business world, especially in increasing consumer purchasing intentions. KOLs are now widely used in various sectors, including the gaming industry. One of them is the presence of Halo Gamers, a YouTube channel that focuses on gaming product reviews. Since 2017, Halo Gamers has targeted the Indonesian gaming market, driven by government projections to control 50% of the gaming industry market share. With more than 2,700 subscribers and collaboration with 16 brands as of November 2024, Halo Gamers acts as a successful KOL in promoting gaming products. Obstacles arise, especially in managing all content portfolios owned by channel owners and information regarding collaboration with brands that are spread across various platforms without centralized media that makes it difficult for channel owners to collaborate with related parties. To overcome this, the author developed a website with the RAD method (a common and popular method in system development that starts from the requirement planning, user design, construction to implementation stages) which functions as a centralized container for Halo Gamers, allowing brands to access portfolios and published content, as well as expanding opportunities for future collaboration at the address halogamers.info.